SEXUAL ETHICS AND RITUAL IN BUGINESE MANUSCRIPT CULTURE: QUR’ANIC PERFORMATIVE PRACTICES IN THE ASSIKALAIBINENG HERITAGE OF SULAWESI - Basri, Basri; Hairul, Moh. Azwar; Asaad, Misbahuddin (MUSHAF: Jurnal Tafsir Berwawasan Keindonesiaan, 2025)
In Islam, sexual intercourse within marriage is regulated as an act of worship. It is not merely viewed as a biological activity but as a means of fulfilling human nature's innate needs. According to hadith, couples are encouraged to recite specific prayers derived from prophetic traditions. Among the Buginese Muslims, however, the practice of sexual preparation has been transformed into a cultural tradition, adapting Islamic teachings through their indigenous Lontara script in a text known as Assikalaibineng, which incorporates Qur’anic verses. This study aims to analyze the Qur’anic invocations in the manuscript by, first, examining and analyzing its philological aspects and, second, employing reception theory to scrutinize the transmission and transformation of Qur’anic practices. The primary data consists of three manuscripts preserved by Muhlis Hadrawi. The findings reveal that the Buginese hermeneutical engagement with the Qur’an in the manuscript involves several adaptations: phonological negotiation of Qur’anic verses to align with regional linguistic patterns, metaphorical interpretations of verses (such as the kun fayakun invocation), symbolic use of Qur’anic letters (e.g., alif and ba), and semantic shifts that assign context-specific meanings to the text. The transmission of the ideas in the manuscript has evolved from an elite, exclusive practice to a more widely communal one, blending mystical elements with cognitive psychology. The Buginese believe that performing the Assikalaibineng ritual can confer religious merit through marital relations, as well as honor one’s spouse, thereby unifying the heart, soul, body, and mind. This study further demonstrates how the integration of religious and cultural elements in this practice has shaped a distinctive feature of Buginese identity. Additionally, it underscores a nuanced understanding of diverse cultural expressions within Islamic traditions.